2013
DOI: 10.1007/s00424-013-1315-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of TMEM16A (ANO1) and TMEM16F (ANO6) in cell migration

Abstract: Members of the TMEM16 family have recently been described as Ca2+-activated Cl− channels. They have been implicated in cancer and appear to be associated with poor patient prognosis. Here, we investigate the role of TMEM16 channels in cell migration, which is largely unknown. We focused on TMEM16A and TMEM16F channels that have the highest expression of TMEM16 channels in Ehrlich Lettre ascites (ELA) cells. Due to the lack of specific pharmacological modulators, we employed a miRNA approach and stably knocked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 40 publications
2
62
0
1
Order By: Relevance
“…Migration analysis in ELA cells after knockdown of either ANO1 or ANO6 showed that the directional cell migration involves ANO1 and that the migration rate involves ANO6. 156 Figure 16 shows relative wound density over time monitored in 2 pancreatic ductal adenocarcinoma cell lines (AsPC-1; BxPC-3) following ANO1 siRNA knockdown. 120 ANO1 knockdown resulted in a decreased migratory rate.…”
Section: Migration and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Migration analysis in ELA cells after knockdown of either ANO1 or ANO6 showed that the directional cell migration involves ANO1 and that the migration rate involves ANO6. 156 Figure 16 shows relative wound density over time monitored in 2 pancreatic ductal adenocarcinoma cell lines (AsPC-1; BxPC-3) following ANO1 siRNA knockdown. 120 ANO1 knockdown resulted in a decreased migratory rate.…”
Section: Migration and Metastasismentioning
confidence: 99%
“…120 ANO1 knockdown resulted in a decreased migratory rate. Although many studies have shown the importance of ANO1 in migration 137,139,141,145,146,156 there are also studies demonstrating that ANO1 might act indirectly. Thus, Ubby et al overexpressed ANO1 in HEK293 cells and measured large ANO1-like currents, but no effect on migration was observed.…”
Section: Migration and Metastasismentioning
confidence: 99%
“…Certain members of this family, such as ANO1, ANO2 and ANO6, can be activated by increases in intracellular [Ca 2+ ] and are classified as Ca 2+ -activated chloride channels (CaCCs) [70][71][72]. CaCCs exhibit voltage dependence, outward rectification and are perhaps best known for their role in Ca 2+ -dependent Cl -secretion in various epithelial tissues.…”
Section: Ano1 Cell Migration and Cystic Fibrosismentioning
confidence: 99%
“…Indeed, ANO1 and ANO6 have been respectively shown to influence the direction and the speed of migration in Ehrlich-Lettre ascites cells, a cell model commonly used in cancer studies. 280 Specific knockdown of ANO1 by siRNA transfection of rat mesenteric arteries was recently demonstrated to abrogate both "classical" I Cl(Ca) and I Cl.cGMP and to inhibit spontaneous cyclical vasomotion as well as agonist-and KCl-induced contractions of small arteries. 139 Surprisingly, downregulation of ANO1 also reduced the expression at the mRNA level of bestrophins, previously shown to be involved in the generation of I Cl.cGMP and the elicitation of rhythmic vasoconstrictions in this vascular bed, 125,129 and the expression of Ca V 1.2 mRNA.…”
Section: Potential Role Of Caccs and Ano1 In Pulmonary Hypertensionmentioning
confidence: 99%